CO2 emissions and militarization in G7 countries: panel cointegration and trivariate causality approaches - Bildirici, Melike (CAMBRIDGE UNIV PRESS, 2017)
This paper aims to test the relation among militarization, CO2 emissions, economic growth and energy consumption in G7 countries from 1985 to 2015 via panel methods. Long- and short-run coefficients and the causal relationship between the variables are important for G7 countries' energy policies and strategy. Cointegration among CO2 emissions, militarization, energy consumption and economic growth was determined by using panel Johansen and panel autoregressive distributed lag (PARDL) methods. Further, the panel trivariate causality test was applied and unidirectional causalities from militarization to CO2 emissions and from energy consumption to CO2 emissions were found. The evidence of bidirectional causality between per capita GDP and militarization, between per capita GDP and energy consumption, and between energy consumption and militarization was determined. The paper recommends that environmental and energy policies must recognize the differences in the relation between militarization, energy consumption and economic growth in order to maintain sustainable economic growth in the G7 countries.
Keywords: CARBON-DIOXIDE EMISSIONS; ECONOMIC-GROWTH; ENERGY-CONSUMPTION; ECOLOGICAL FOOTPRINTS; ENVIRONMENTAL-QUALITY; OIL CONSUMPTION; KUZNETS CURVE; TESTS; DESTRUCTION; NATIONS; Business & Economics; Environmental Sciences & Ecology